Pengembangan Media ‘Economic Monopoly’ Berbasis Game Untuk Mata Pelajaran Ekonomi Kelas X SMAN 1 Singosari - Endah Nur Amalina; Ro'ufah Inayati (Universitas Negeri Surabaya, 2021)
Digital technology-based learning media has not been widely used yet in SMA Negeri 1 Singosari. The economic subject learning process used by the teachers in SMA Negeri 1 Singosari, in textbooks and PowerPoint, does not maximize the facilities and potential available in this digital era, hindering students' capability in learning well. The school rules that do not prohibit students from bringing smartphones to school and the development of media and technology can minimize the obstacle. This research and development aim to develop an android game-based learning media called